Mechanizmy srocnoj adaptacii sportsmenov k vozdejstvijam fiziceskich nagruzok - Denisenko, Ju. P. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
During long-term researches the author revealed the existence of the nonspecific brake-relaxational functional system of the term adaptation and protection (BRFSTAP) of an organism against the extreme influences of big physical, hypoxic and hyperthermal loadings.